Tinjauan Yuridis Terhadap Pemberian Kredit Tanpa Agunan Untuk Modal Usaha Dengan Prudential Principle dan The Five C of Credit Analysis - Wiwit Rahmawati; Ramlani Lina Sinaulan; Januar Agung Saputera (Faculty of Sharia and Law State Islamic University Syarif Hidayatullah Jakarta, 2022)
When extending credit to consumers, banks and financial institutions will always take precautions to protect themselves if the credit recipient (debtor) defaults or is unable to repay the credit. If the credit is followed by the binding of collateral, this prevention occurs. If the debtor defaults, the guarantee will serve as a replacement for credit payments made by banks and other financial institutions. In accordance with Article 2 letter b of Law No. 10 of 1998 pertaining to Banking, a violation of the precautionary principle in the provision of credit by banks carries legal repercussions, including the imposition of criminal punishment or fines. This study employs a qualitative descriptive methodology. According to the findings of this study, the granting of credit by banks needs cautious action on the part of the bank. The risk associated with extending credit is so large that it is necessary to evaluate whether the prospective debtor is deserving of credit. In banking practice, both persons and legal entities can apply for credit. Each candidate must satisfy the bank's predetermined criteria.